A case report of splenic injury related to colonoscopy: Fortunately treated with conservative treatment - Kazuya Moriwake; Hiroshi Isozaki; Takehiro Takama; Shigeki Murakami; Sasau Matsumoto (DEN Open)
Abstract Colonoscopy is a common procedure for screening of colon cancer. Although complications are rare, recently there have been reports of splenic injury associated with colonoscopy. Its causes are not clear. Herein, we report an 84‐year‐old man who underwent a colonoscopy for an annual routine examination. The colonoscopy was performed with moderate difficulty due to loop formation and took about 50 min. After the examination, he developed syncope, sweating, and abdominal distention with low blood pressure. Plain computed tomography revealed ascites, and the patient was hospitalized with close monitoring. The following day, his hemoglobin level was decreased by about 3.0 g/dL. Contrast‐enhanced computed tomography revealed the splenic injury. The patient was hemodynamically stable and was treated conservatively. Splenic injury is an uncommon complication of colonoscopy; however, it may cause hemodynamic instability. Physicians performing colonoscopies should be aware of this potential complication.